Ligninolytic enzymes production during polycyclic aromatic hydrocarbons degradation: effect of soil pH, soil amendments and fungal co-cultivation - Vipotnik, Ziva (2021)
Soil microorganisms play an important role in the degradation of PAHs and use various metabolic pathways for this process. The effect of soil pH, different soil amendments and the co-cultivation of fungi on the degradation of PAHs in soil and on the activity of ligninolytic enzymes was evaluated. For that purpose, three fungi were studied: Trichoderma viride, Penicillium chrysogenum and Agrocybe aegerita. Biodegradation assays with a mixture of 200 ppm PAHs (fluorene, pyrene, chrysene, and benzo[a]pyrene---50 ppm each) were set up at room temperature for 8 weeks. The maximum laccase activity by solid state fermentation---SSF (7.43 U/g) was obtained by A. aegerita on kiwi peels with 2 weeks and the highest manganese peroxidase activity (7.21 U/g) was reached in 4 weeks, both at pH 7. Fluorene, pyrene, and benzo[a]pyrene achieved higher degradation rates in soil at pH 5, while chrysene was more degradable at pH 7. About 85--90\% of the PAHs were degraded by fungal remediation. The highest degradation of fluorene was achieved by co-cultivation of A. aegerita and P. chrysogenum, remaining 14\% undegradable. Around 13\% of pyrene stay undegradable by A. aegerita and T. viride and by A. aegerita and P. chrysogenum, both systems supported in kiwi peels, while 11\% of chrysene remained in soil by the co-cultivation of these fungi, supported by peanut shells. Regarding benzo[a]pyrene, 13\\% remained in soil after treatment with A. aegerita. Despite the increase in degradation of some PAHs with co-cultivation, higher enzyme production during degradation was observed when fungi were cultivated alone.